PENGARUH BUDAYA ORGANISASI DAN ASIMETRI INFORMASI TERHADAP PARTISIPASI ANGGARAN YANG MEDIASI KESENJANGAN ANGGARAN - Langgeng Prayitno Utomo (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2020)
This study aims to determine the direct effect of information asymmetry and organizational commitment on budget participation through budget gaps and the indirect effect of information asymmetry and organizational commitment on budget participation through budget gaps. The population of this study were all employees at 28 Koperasi Pegawai Republik Indonesia (KPRI). The total sample of 122 respondents was selected through purposive sampling. Methods of data collection through methods using questionnaires and literature study. The results showed that information asymmetry has no direct effect on budget participation. Organizational commitment affects budget participation and organizational commitment affects budget gaps. In addition, organizational commitment and budget participation do not directly affect budget gaps. Information asymmetry and information commitment through budget participation have no effect on budget gaps. Increasing participation in budgeting is considered to reduce budgetary slack. The participation budget can also improve the performance of employees or employees because they feel responsible for the budget that is jointly prepared.